Haemorheological parameters in patients with retinal artery occlusion and anterior ischaemic optic neuropathy. - Wiek, J (1992)
The haemorheological parameters haematocrit (Hct), plasma viscosity (PV), red cell aggregation (RCA), red cell filterability (RCF), apparent whole blood viscosity (WBV), and fibrinogen were measured in 31 patients with retinal artery occlusion (RAO), 25 patients with anterior ischaemic optic neuropathy (AION), and 19 patients with giant cell arteritis (GCA). The patient groups were compared with controls of same age and similar prevalence of cardiovascular risk factors. Patients with RAO and AION have a significantly decreased RCF in comparison with controls. All other parameters showed no differences. Patients with GCA had significantly decreased Hct and RCF and increased PV and fibrinogen. After 2 weeks of systemic treatment with high dose steroids in patients with GCA the plasma viscosity had returned to normal and was even lower than in controls, and the Hct and fibrinogen had reached normal levels.